Integrating Green Marketing Strategies with the Philosophy of Memayu Hayuning Bawana in Javanese Islamic Culture - Daryono Daryono; Adijati Utaminingsih; Witjaksono E. H.; Willyanto Kartiko Kusumo (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2026)
This research is driven by the environmental challenges posed by the liquid waste generated by batik micro, small, and medium enterprises (MSMEs) in Semarang City. The primary objective of this study is to analyze the integration of Green Marketing (GM) strategies with the philosophy of Memayu Hayuning Bawana (MHB) within the context of Javanese Islamic culture, focusing specifically on batik MSMEs in Semarang City. This analysis is grounded in local Javanese wisdom that aligns with Islamic teachings, rather than relying on the Qur'an or Hadith. Employing a qualitative research methodology, this study adopts a single case study design analyzed through the Theory of Planned Behavior. A purposive sampling technique has been utilized to select informants from batik MSMEs who possess either residency in or familiarity with Javanese Islamic cultural practices. Data collection methods include observation, in-depth interviews, documentation, and focus group discussions. Through the application of this methodology, the study presents a model for integrating GM strategies with the MHB philosophy as practiced by batik MSMEs in Semarang City. This model is articulated through four principal findings: First, Eco-Philosophy Integration Model. This concept emphasizes the implementation of MHB philosophy within green marketing as a sustainable business model. Second, Active Patience Concept. This notion reinterprets the traditional understanding of "patience," transitioning it from a passive interpretation to one characterized by active strategic thinking. Third, Value-Driven Business Paradox. This phenomenon highlights how businesses driven by MHB moral values can achieve considerable social and ecological impacts, even in the presence of modest financial returns, thereby creating alternative success metrics. Fourth, Cultural-Modern Communication Gap. This finding identifies the discrepancies between the comprehension of MHB philosophy and the pragmatic mindset of contemporary consumers. The four primary findings, representing a model for the integration of GM strategies with the MHB philosophy in Javanese Islamic culture, are intended to provide valuable strategic contributions to batik MSMEs in Semarang City.